Hormesis: Wound healing and keratinocytes - Edward J. Calabrese; Gaurav Dhawan; Rachna Kapoor; Evgenios Agathokleous; Vittorio Calabrese (Elsevier, 2022)
Hormetic dose responses (i.e., a biphasic dose/concentration response characterized by a low dose stimulation and a high dose inhibition) are shown herein to be commonly reported in the dermal wound healing process, with the particular focus on cell viability, proliferation, and migration of human keratinocytes in in vitro studies. Hormetic responses are induced by a wide range of substances, including endogenous agents, numerous drug and nanoparticle preparations and especially plant derived extracts, including many well-known dietary supplements as well as physical stressor agents, such as low-level laser treatments. Detailed mechanistic studies have identified common signaling pathways and their cross-pathway communications that mediate the hormetic dose responses. These findings suggest that the concept of hormesis plays a fundamental role in wound healing, with important potential implications for agent screening and evaluation, as well as clinical strategies.